IMMEDIATE LOADING WITH PROVISIONALIZATION IN AESTHETIC AREA - Lacerda, Fernanda dos Santos; Machado, Thaís Dias; dos Santos, Luana Thamires Rocha; Pinto, Lorenzo Mendonça; Martins, Maíra Menezes Santos; Heggendorn, Fabiano Luiz (Seven Editora, 2025)
Oral rehabilitation with dental implants, especially in the aesthetic area, has evolved with the immediate loading approach, aiming to restore function and aesthetics, minimizing bone resorption, and preserving peri-implant soft tissues. This study aimed to review the scientific literature on the predictability of immediate implant loading in the maxillary aesthetic zone, highlighting its impact on peri-implant tissue maintenance and the factors that influence its clinical success. The research followed a bibliographic, exploratory, and qualitative methodology, reviewing articles published between 2020 and 2025. The results indicated that immediate loading demonstrates benefits in preserving peri-implant soft and hard tissues, with less mucosal alteration and reduced papillary recession compared to delayed loading. Additionally, the use of connective tissue grafts in cases of vestibular bone loss has proven effective, ensuring stability and aesthetic predictability. The three-dimensional position of the implant and preservation of peri-implant tissue volume are also crucial to the success of the procedure. Long-term analysis reinforces the effectiveness of immediate loading in maintaining gingival architecture and preserving peri-implant tissues. The conclusion suggests that immediate loading is a promising approach, but that careful case selection and implementation of appropriate clinical protocols are essential for treatment success. DOI: https://doi.org/10.56238/sevened2025.029-021